Librarians Skills and Competencies for Scholarly Communication and Repository Management in Nigeria - et.al, Usman Ahmed Adam (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The rapid change in scholarly communication and knowledge management has transformed the repository services and imposed new skills and competencies for repository management. This study is posed to assess the skills and competencies of librarians for repository management and scholarly communication in academic institutions in Nigeria. The study adopted a survey research design to assess the skills and competencies of the librarians using NASIG “Core Competencies for Scholarly Communication Librarians 2017”. The sample size of the study comprises 120 librarians across 40 institutions. The findings of the study indicate among others that; 74 % of the librarians have a general understanding of repository platforms, 54.17% background knowledge of open access movement, and 58% experience in advocacy for open access. At the same time, 83.3% of the librarians can capture, store, and preserve the research output. While 62.3% understand research impact, only 35.8% understand emerging alternatives measures of the impact. Although, 73.1 % understand Data description and storage, only 20.8% understand text and data mining. The study concluded that awareness, skills, and competencies of the librarians is increasing and recommends among others; setting up a framework for the employment of repository and scholarly communication librarians and training on repository management and scholarly communication.